Between Inhabited Interiors and Interiors on Display: Exploring Spatial Boundaries at Rosenborg Castle - Pilegaard, Ane (UI Scholars Hub, 2021)
When visiting museums, we meet various types of physical barriers, such as glass vitrines, railings, and extended ropes, which have been put there to protect the objects on display. Such barriers are often accused of creating an unfavourable distance to museum objects but can also be thought of in more positive terms, as this article will seek to demonstrate. Based on analyses of museum display boundaries at Rosenborg Castle in Copenhagen, where visitors can experience objects from The Royal Danish Collection within historic interiors, the article looks into the effects of such boundaries on the museum experience. The article explores the particular threshold experiences that take place at Rosenborg where you constantly fluctuate between, on the one side, looking at objects and interiors that have been put on display in front of you, and, on the other, being inside the historic interiors. It argues that this spatial ambiguity opens up productive, albeit obscure, in-between spaces for the museum visitor to inhabit and points to the importance of truly attending to the design of display boundaries when creating museum exhibitions.